2017
DOI: 10.1016/j.jcps.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Speaking to the heart: Social exclusion and reliance on feelings versus reasons in persuasion

Abstract: The authors of this study identify an alternative frame of communication for persuading people who feel socially excluded to behave in ways that benefit individual and social wellbeing, regardless of future connection possibilities. The authors suggest that socially excluded (included) consumers tend to rely on affect (cognition) in processing information, and to consequently prefer persuasive messages based on feelings (reasons). The effect occurs because people tend to ruminate about exclusionary events, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 54 publications
0
34
1
Order By: Relevance
“…This may be because social rejection activates a hostile mindset that increases the tendency to view others as aggressive (e.g., DeWall et al, 2010;DeWall, Twenge, Gitter, & Baumeister, 2009), or it may be because rejection causes individuals to inaccurately believe that the inclusive others had engaged in exclusion (Chernyak & Zayas, 2010). Other research, however, showed that rejected individuals may act pro-socially or cooperatively towards those who might provide renewed social connection (De Cremer, 2002;De Cremer & Leonardelli, 2003;Lee, & Shrum, 2012;Maner et al, 2007) to satisfy the need to belong (Lu & Sinha, 2017;Smart & Leary, 2009). These findings are valuable, but one implicit assumption that this literature makes is that social rejection is an 'individual social experience'.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be because social rejection activates a hostile mindset that increases the tendency to view others as aggressive (e.g., DeWall et al, 2010;DeWall, Twenge, Gitter, & Baumeister, 2009), or it may be because rejection causes individuals to inaccurately believe that the inclusive others had engaged in exclusion (Chernyak & Zayas, 2010). Other research, however, showed that rejected individuals may act pro-socially or cooperatively towards those who might provide renewed social connection (De Cremer, 2002;De Cremer & Leonardelli, 2003;Lee, & Shrum, 2012;Maner et al, 2007) to satisfy the need to belong (Lu & Sinha, 2017;Smart & Leary, 2009). These findings are valuable, but one implicit assumption that this literature makes is that social rejection is an 'individual social experience'.…”
Section: Discussionmentioning
confidence: 99%
“…A large body of research shows that social rejection threatens the need to belong (Gonsalkorale & Williams, 2007;Goodwin, Williams, & Carter-Sowell, 2010;Williams, 2007;Zadro, Williams, & Richardson, 2004), an extremely basic and powerful human need (Baumeister & Leary, 1995;Maslow, 1943). When the need to belong is threatened by social rejection, the rejected individuals are motivated to pursue social connection so as to re-establish their belongingness (Lu & Sinha, 2017;Smart & Leary, 2009;Tai, Zheng, & Narayanan, 2011). Some research showed that rejection led individuals to be more attentive towards socially related information (Bernstein, Sacco, Brown, Young, & Claypool, 2010).…”
Section: Co-experience Of Rejection Need To Belong and Cooperationmentioning
confidence: 99%
“…Affects refer to feelings or emotions, and information processing based on affects is automatic and faster. Meanwhile, cognition involves reasons and logics, and information processing based on cognition is deliberate and consumes more cognitive resources [ 53 ]. For consumers who experience loneliness, our review suggests that loneliness impair individuals’ cognitive thinking, which makes affective persuasions more effective to emotionally vulnerable consumers.…”
Section: Lonely Consumers: Psychological Commercial and Social Immentioning
confidence: 99%
“…For consumers who experience loneliness, our review suggests that loneliness impair individuals’ cognitive thinking, which makes affective persuasions more effective to emotionally vulnerable consumers. In other words, consumers tend to rely on feelings and emotions to process external information and, thus, the affect-based messages may be more effective in swaying lonely consumers’ product choices [ 53 ].…”
Section: Lonely Consumers: Psychological Commercial and Social Immentioning
confidence: 99%
See 1 more Smart Citation